A kidney injury molecule‐1 (Kim‐1) gene reporter in a mouse artificial chromosome: the responsiveness to cisplatin toxicity in immortalized mouse kidney S3 cells. (October 2016) - Kokura, Kenji; Kuromi, Yasushi; Endo, Takeshi; Anzai, Naohiko; Kazuki, Yasuhiro; Oshimura, Mitsuo; Ohbayashi, Tetsuya
Abstract: Background: Kidney injury molecule‐1 (Kim‐1) has been validated as a urinary biomarker for acute and chronic renal damage. The expression of Kim‐1 mRNA is also activated by acute kidney injury induced by cisplatin in rodents and humans. To date, the measurement of Kim‐1 expression has not fully allowed the detection of in vitro cisplatin nephrotoxicity in immortalized culture cells, such as human kidney‐2 cells and immortalized proximal tubular epithelial cells. Methods: We measured the augmentation of Kim‐1 mRNA expression after the addition of cisplatin using immortalized S3 cells established from the kidneys of transgenic mice harboring temperature‐sensitive large T antigen from Simian virus 40. Results: A mouse Kim‐1 gene luciferase reporter in conjunction with an Hprt gene reporter detected cisplatin‐induced nephrotoxicity in S3 cells. These two reporter genes were contained in a mouse artificial chromosome, and two luciferases that emitted different wavelengths were used to monitor the respective gene expression. However, the Kim‐1 reporter gene failed to respond to cisplatin in A9 fibroblast cells that contained the same reporter mouse artificial chromosome, suggesting cell type‐specificity for activation of the reporter. Conclusions: We report the feasibility of measuring in vitro cisplatin nephrotoxicity using a Kim‐1 reporter gene in S3 cells.